THE THIRD WORLD WAR : AUGUST 1985 - Muller, V.C. (Scientia Militaria - South African Journal of Military Studies, 2011)
This scenario of the Third World War depicts the events leading to the war, the conflict itself, and the aftermath. Purporting to be a history, complete with appendices, maps and index, of a war recently ended, the overall tone of the book gives the impression that it might have been derived from one or more war games.